2021
DOI: 10.1016/j.paid.2021.111132
|View full text |Cite
|
Sign up to set email alerts
|

Is psychological flexibility a mediator between perceived stress and general anxiety or depression among suspected patients of the 2019 coronavirus disease (COVID-19)?

Abstract: This study is aimed to investigate the status of general anxiety and depression among suspected patients of COVID-19 and explore whether psychological flexibility can serve as a mediator between perceived stress and general anxiety or depression. Total of 180 participants completed the online questionnaire which comprised demographic information, the Perceived Stress Scale (PSS), the 7-item Generalized Anxiety Disorder scale (GAD-7), the 9-item Patients Health Questionnaire (PHQ-9), the Acceptance and Action Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 36 publications
5
22
0
4
Order By: Relevance
“…This is consistent with previous literature that showed that higher perceived stress was associated with lower psychological flexibility [ 44 ]. We also found that lower psychological flexibility was associated with higher levels of anxiety and depression, which is in line with previous studies that suggested that lower psychological flexibility was associated with more depressive symptoms, more anxiety-related symptoms, and poorer psychological health in general [ 45 ]. In this line, several studies found how depression, stress, anxiety, loneliness, and neuroticism are parameters related to mental illness [ 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous literature that showed that higher perceived stress was associated with lower psychological flexibility [ 44 ]. We also found that lower psychological flexibility was associated with higher levels of anxiety and depression, which is in line with previous studies that suggested that lower psychological flexibility was associated with more depressive symptoms, more anxiety-related symptoms, and poorer psychological health in general [ 45 ]. In this line, several studies found how depression, stress, anxiety, loneliness, and neuroticism are parameters related to mental illness [ 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…There is recent research on mitigating the effects of COVID-19 and improving mental health and wellbeing. Interventions that promote Psychological Flexibility, such as Acceptance and Commitment Therapy (ACT) and Mindfulness are shown to be effective [19,[46][47][48], and also mitigate the effects of ACEs [49,50]. Psychological Flexibility, the ability to adapt to situations by accepting and fully experiencing all thoughts and feelings and engaging in value-based behaviour, aims to promote positive mental health and wellbeing and reduces psychological distress [51].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it was hypothesized that those with no ACEs will have significantly lower stress at Time 2 when compared to those with ACEs. Finally, this study aims to investigate whether self-reported Psychological Flexibility is a protective factor that can help mitigate the negative impacts of ACEs and psychological distress on wellbeing over time, due to the known positive relationship between psychological wellbeing and psychological flexibility [46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the presence of high psychological inflexibility determines the implementation of avoidance strategies (Dawson & Golijani-Moghaddam, 2020 ). In addition, psychological inflexibility has been successfully tested as a mediator in the relationship between different constructs such as COVID-19 stress and psychological distress (i.e., depression, anxiety, and somatization) (Arslan et al, 2021 ), perceived stress, anxiety, and depression (Huang et al, 2021 ), intolerance of uncertainty, and PTSD symptoms (Kennedy et al, 2021 ). One limitation is that the potential mediating role of psychological inflexibility in the relationship between perceived stress and PTSD symptoms in any stressful situation, as well as in the context of COVID-19 Pandemic, has not been examined.…”
Section: Introductionmentioning
confidence: 99%